First results of Central Asiatic Euchalcia DNA-studies: comparison of nucleotide sequence differences in COI between Euchalcia herrichi and Euchalcia gyulai (Lepidoptera: Noctuidae) - Korb, Stanislav K. (Acta Biologica Sibirica, 2020)
We submitted first results of the DNA studies of the Central Asiatic owlet moths of the genus Euchalcia. Standard cytochrome C oxidase subunit I (COI) gene fragments were sequenced for DNA barcoding of six specimens belonging to Euchalcia herrichi and Euchalcia gyulai. We compared the received sequences between discussed species and with two European Euchalcia species (E. variabilis and E. consona). We found no variability within the COI sequences of the samples collected in the same locality (Alai Mts., Kyrgyzstan), whereas the difference in COI sequences between two populations (Ketmen Mts., Kazakhstan and Alai Mts., Kyrgyzstan) was 0.005.